Perlindungan Hukum Debitur Perbangkan Akibat Wanprestasi Perjanjian Kredit Masa Pandemi - Aloysia A, Ruth; Prananda, Rahandy Rizki (Fakultas Syariah INSURI Ponorogo, 2023)
This study is to determine what kind of efforts are obtained legally against bank customers in bad credit problems during the pandemic and whether execution is a final solution in a bad credit problem, using normative legal research methods, it was concluded that the protection of debtors who have access to credit facilities during the Covid-19 pandemic includes; First, the government issued a policy in the form of Presidential Regulation No. 12 of 2020, which concerns the determination of Corona virus disease in natural disasters nationally in 2019. The spread of natural disasters (Covid-19). Regulation of the Financial Services Authority of the Republic of Indonesia Number 11/POJK.03/2020, . regarding the impact of the national economic stimulus counter cyclical policy on the spread of the corona virus disease in 2019, by itself Law No. 8 of 1999 Consumer legal protection, including debtors, is guaranteed according to the provisions. 2. The bank's actions in assisting the settlement of bad loans during the Covid-19 pandemic have several stages, so legal protection to debtors applies, so banks do not necessarily execute debtors' collateral or guarantees. However, banks provide settlement solutions to bad debtors so that the ability to pay the stuck debtors will slowly return to normal during this pandemic, so that the bad collectibility can become smooth, namely through the Restructuring process.